2017
DOI: 10.1080/17435390.2017.1306893
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative biokinetics of titanium dioxide nanoparticles after oral application in rats: Part 2

Abstract: The biokinetics of a size-selected fraction (70 nm median size) of commercially available and V-radiolabeled [V]TiO nanoparticles has been investigated in female Wistar-Kyoto rats at retention timepoints 1 h, 4 h, 24 h and 7 days after oral application of a single dose of an aqueous [V]TiO-nanoparticle suspension by intra-esophageal instillation. A completely balanced quantitative body clearance and biokinetics in all organs and tissues was obtained by applying typical [V]TiO-nanoparticle doses in the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 35 publications
6
119
0
Order By: Relevance
“…In contrast, the study performed in rats did not show any significant increase of titanium in liver, spleen, kidney and even brain in comparison with the vehicle control group, and no dose–response relationship was observed after nano‐TiO 2 (264.4, 520.8 and 1041.5 mg/kg bw/day) was orally administered daily for 13 weeks . However, a more recent study using radiolabelled nano‐TiO 2 showed nano‐TiO 2 distribution in rat liver, lungs, kidneys, brain, spleen, uterus and skeleton 7 days after administration of a single dose of nano‐TiO 2 (about 40 μg/kg bw), even if the estimated absorbed dose was low (0.09–0.98 ng/g depending on the organ) . These results suggested that upon repeated long‐term oral exposure, nano‐TiO 2 may accumulate in specific organs and thereby present a risk in humans who are orally exposed to nano‐TiO 2 .…”
Section: Absorption and Distributionmentioning
confidence: 80%
See 4 more Smart Citations
“…In contrast, the study performed in rats did not show any significant increase of titanium in liver, spleen, kidney and even brain in comparison with the vehicle control group, and no dose–response relationship was observed after nano‐TiO 2 (264.4, 520.8 and 1041.5 mg/kg bw/day) was orally administered daily for 13 weeks . However, a more recent study using radiolabelled nano‐TiO 2 showed nano‐TiO 2 distribution in rat liver, lungs, kidneys, brain, spleen, uterus and skeleton 7 days after administration of a single dose of nano‐TiO 2 (about 40 μg/kg bw), even if the estimated absorbed dose was low (0.09–0.98 ng/g depending on the organ) . These results suggested that upon repeated long‐term oral exposure, nano‐TiO 2 may accumulate in specific organs and thereby present a risk in humans who are orally exposed to nano‐TiO 2 .…”
Section: Absorption and Distributionmentioning
confidence: 80%
“…Using an ex vivo model of porcine oral mucosa, nano‐TiO 2 was shown to rapidly interact with the mucous layer, penetrate the oral epithelium and impact on the physiological homeostasis of buccal/sublingual cells in the oral cavity . Three studies performed in vivo in rats showed that oral administration of nano‐TiO 2 either led to extremely low systemic absorption of nano‐TiO 2 from the gastrointestinal tract or did not lead to significant nano‐TiO 2 absorption . The nano‐TiO 2 dose absorbed across the intestinal barrier was estimated to be about 0.6%, 0.2% and 0.05% of the administered dose only, respectively, 1 h, 4 h and 7 days after administration .…”
Section: Absorption and Distributionmentioning
confidence: 99%
See 3 more Smart Citations